(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2020)
The Temporal Agreement in the subjunctive subordinate clauses suffers many violations in Spanish as in French. Linguists have different points of view about the phenomenon and we agree with Hanssen (1913), Gili Gaya (1943), Brunot (1953), Farley (1965), Obaid (1967), Farley (1970), Suñer and Padilla Rivera (1990), and Carrasco (1994), among others, that, in many cases the prescriptive norms are not fulfilled. On the other hand, these rules are very similar in both languages, whereas their real uses differ from one language to another. This article attempts to analyze the so-called temporal agreement in the subjunctive subordinate clauses in Spanish and French, from a descriptive contrastive approach. We intend to draw attention to the breach of prescriptive norms in both languages and the contradictions that emerge from the interlinguistic contrast indirectly affecting the very (in)definition of the subjunctive mode. Keywords: Spanish and French subjunctive, temporal agreement, verbal mode, contrastive linguistics.